A deep dive into the surgical and pharmacological considerations of obesity in chronic myeloid leukemia: a narrative review - Ghasoub, Rola; Elsayed, Basant; Benkhadra, Maria; Saglio, Giuseppe; Cortes, Jorge; Elmarasi, Mohamed; Elsayed, Engy; Elsabagh, Ahmed Adel; Elmakaty, Ibrahim; Elsayed, Abdelrahman; Yassin, Mohamed (Frontiers in Oncology, 2025)
Background/ObjectivesThe rising prevalence of obesity presents significant challenges in managing chronic myeloid leukemia (CML). Bariatric surgery alters the bioavailability of oral medications, necessitating tailored treatment strategies for obese CML patients. This review aims to summarize the existing literature regarding CML management in patients with obesity and related surgeries, providing novel recommendations for their medical and surgical management.MethodsA narrative review was performed, analyzing English-language articles published up to 2024. Key aspects considered included the impact of obesity and surgery on the pharmacokinetics (PK) of tyrosine kinase inhibitors (TKIs), potential drug-drug interactions (DDIs) with weight loss medications, and the role of therapeutic drug monitoring (TDM). The review also examined the implications of obesity on CML patient outcomes and treatment milestones, aiming to establish a pathway for managing these patients.Results/DiscussionClinical data on CML management in obese patients is limited. Gastric bypass surgery may impair TKI efficacy due to reduced gastric acid secretion, affecting drug absorption. Adjustments like deflating gastric bands may enhance TKI absorption. The concurrent use of proton pump inhibitors can significantly lower the efficacy of certain TKIs, while others can be safely co-administered. Notably, patients with prior bariatric surgery show delayed treatment response milestones and may require TKI dose adjustments based on molecular responses rather than TDM.ConclusionPatients with CML planning bariatric surgery should receive comprehensive preoperative counseling regarding its effects on TKI therapy. Achieving deep remission pre-surgery is advisable, and delaying procedures when malabsorption is anticipated may enhance treatment outcomes. A multidisciplinary approach is essential in considering weight-loss medications, with further research needed to optimize TKI dosing in this population.